Pesticide Use by Vegetable Growers in Rupandehi District, Western Nepal: Environmental and Health Risk Effects - Thapa, Chandra Bahadur; Gubhaju, Munesh Ratna; Marasini, Sanjaya (Butwal Campus Journal, 2024)
Rupandehi district, located in the southern part of western Nepal, is well-known for producing different kinds of vegetables and has many commercial vegetable-growing pocket areas. This study aims to identify the types of pesticides used and their effect on human health and environment. The data were collected using semi-structured interviews with 150 vegetable growers, 40 pesticide retailers, and focus group discussions with key informants. This study found that the vegetable growers used insecticides with 25 technical names; fungicides with 10 technical names; and herbicides with 4 technical names. The maximum vegetable growers (40%) experienced respiratory tract irritation, followed by skin disorders (20%), asthma (13%), gastrointestinal disorders (12%), eye irritation (10%), and neurological effects (9%) in the study area. Similarly, air, water, and land pollution were found in the study area mainly due to the improper pesticide use and disposal of pesticide containers. Most of the vegetable growers (47%) illegally disposed of pesticide containers, followed by burning in the field (28%), storing foodstuffs (10%), putting oil (7%), selling to recyclers (5%), and burying in the field (3%). This study may provide baseline information for pesticide management and utilization in this area, and there is an urgent need for a thorough investigation into the harmful effects of pesticides on farmer health and pesticide residues in vegetables.